Modern communication systems using MATLAB - Proakis, John G. (Cengage Learning, 2013)
Contemporary Communication Systems Using MATLAB.' Featuring a variety of applications that motivate learners, this books serves as a companion or supplement to any of the comprehensive textbooks in communications systems.